LaVO4:Eu3+ nanoparticles show no genotoxicity on fibroblast cultures - Prokopiuk, V.Yu.; Tkachenko, A.S.; Onishchenko, A.I.; Yefimova, S.L.; Maksimchuk, P.O.; Lazurenko, V.V.; Klochkov, V.K. (Abstract book of International Conference "Nanotechnologies and Nanomaterials"NANO-2022, 2022)
Therapeutic efficacy of any drug used in clinical medicine should prevail over its possible toxic effects. One of the manifestations of the negative impact of drugs on cells is genotoxicity, which has to be evaluated in screening of potential drugs, including nanomaterials. The aim of this study was to assess the genotoxicity of lanthanum orthovanadate nanoparticles (LaVO 4 :Eu 3+) on fibroblast cultures. Materials and methods. Genotoxicity was analyzed using the micronucleus assay. According to the protocol, dermal fibroblasts of rat fetuses were cultivated in DMEM enriched with 10% fetal bovine serum in a CO 2 incubator. The cells underwent 3 passages. The cells were transferred into a 24-well plate at 50 000 cells per well. Thereafter, LaVO 4 :Eu 3+ nanoparticles were added (0-30-65-130- 260-520 μg / ml). For a positive control, the cells were incubated with cisplatin. For a negative control, the intact cells were used. Following 72 hours, the fibroblasts were fixed using alcohol and stained (Romanowsky – Giemsa staining). The amount of fibroblasts with micronuclei was analyzed and compared. Statistical analysis was carried out by Kraskel-Wallis and Dunn’s tests. Results. When lanthanum orthovanadate nanoparticles (LaVO 4 :Eu 3+ ) were added to fibroblast cell cultures at concentrations of 30-65-130 μg / ml, the number of cells with micronuclei did not differ statistically significantly from cultures without nanoparticles. Higher concentrations caused cell detachment from the surface and made it impossible to count the number of cells with micronuclei. Cisplatin in the positive control samples caused an increase in the number of cells from micronuclei and promoted changes in the shape of cells and nuclei. Conclusions. LaVO 4 :Eu 3+ nanoparticles demonstrate no genotoxicicty against fibroblast cultures in vitro.
Keywords: nanoparticles; LaVO 4 :Eu 3+; genotoxicity; fibroblast; in vitro